2017
DOI: 10.3389/fgene.2017.00028
|View full text |Cite
|
Sign up to set email alerts
|

Dysbindin Deficiency Modifies the Expression of GABA Neuron and Ion Permeation Transcripts in the Developing Hippocampus

Abstract: The neurodevelopmental factor dysbindin is required for synapse function and GABA interneuron development. Dysbindin protein levels are reduced in the hippocampus of schizophrenia patients. Mouse dysbindin genetic defects and other mouse models of neurodevelopmental disorders share defective GABAergic neurotransmission and, in several instances, a loss of parvalbumin-positive interneuron phenotypes. This suggests that mechanisms downstream of dysbindin deficiency, such as those affecting GABA interneurons, cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 93 publications
1
12
0
Order By: Relevance
“…Family-based association data have identified dysbindin ( DTNBP1 ) as a susceptibility gene for schizophrenia 172 , whose dominant circuit impact is impaired inhibition 173 . Dysbindin KO mice show a reduced number of PV interneurons in hippocampal CA1 173 , 174 , and transcriptome changes of various proteins involved the regulation of intrinsic properties 174 . Recordings from PV interneurons in dysbindin KO mice show a reduction in action potential frequency resulting in a reduced inhibitory drive 126 .…”
Section: Altered Pv Interneuron Activity Is Caused By Changes To Diffmentioning
confidence: 98%
“…Family-based association data have identified dysbindin ( DTNBP1 ) as a susceptibility gene for schizophrenia 172 , whose dominant circuit impact is impaired inhibition 173 . Dysbindin KO mice show a reduced number of PV interneurons in hippocampal CA1 173 , 174 , and transcriptome changes of various proteins involved the regulation of intrinsic properties 174 . Recordings from PV interneurons in dysbindin KO mice show a reduction in action potential frequency resulting in a reduced inhibitory drive 126 .…”
Section: Altered Pv Interneuron Activity Is Caused By Changes To Diffmentioning
confidence: 98%
“…Investigation of transcriptional responses of developing hippocampal neurons in sdy/B6 mutants revealed not only the characteristic GABAergic interneuron deficiency but also changes in expression of the cation-chloride cotransporters NKCC1 and KCC2 during hippocampal development (Larimore et al, 2017). NKCC1 and KCC2 expression changes have been documented in the brains of patients with schizophrenia (Hyde et al, 2011;Sullivan et al, 2015) and NKCC1 agents, including the NKCC1 chloride antagonist bumetanide, have been studied in schizophrenia.…”
Section: Dysbindin-1 and Putative Treatment Strategies For Cognitive mentioning
confidence: 99%
“…BLOC-1 expression in the mouse central nervous system is developmentally regulated with higher expression during perinatal periods ( Ghiani et al, 2010 ), and in its absence, hippocampal neurones in cultures exhibit defective neurite outgrowth ( Ghiani et al, 2010 ; Ito et al, 2010 ; Ma et al, 2011 ). Behavioural and neurophysiological abnormalities have been reported in the sandy mouse, a naturally occuring mutant carrying an in-frame deletion in the gene encoding dysbindin (reviewed by Ghiani and Dell’Angelica, 2011 , for examples see Bhardwaj et al, 2009 ; Cox et al, 2009 ; Ryder and Faundez, 2009 ; Talbot, 2009 ; Papaleo et al, 2012 ; Carr et al, 2013 ; Glen et al, 2014 ; Larimore et al, 2014 , 2017 ; Bhardwaj et al, 2015a ; Yuan et al, 2016 ) as well as in other dysbindin-mutants ( Petit et al, 2017 ; Chang et al, 2018 ). Importantly, Spiegel et al (2015) reported that the pallid and sandy lines show similar impairment of social recognition memory.…”
Section: Introductionmentioning
confidence: 99%